The graphic design reference & specification book - Evans, Poppy, 1949-; Sherin, Aaris (Rockport Publishers, 2013)
The Graphic Design Reference & Specification Book should always be next to a designer's computer. Completely practical with only the most needed information, this valuable book provides designers with all the little details that can make or break a design, such as how much space to leave in the gutter when designing barrel folds, how to layout a template for a box, and the ratios of each part, as well as metric conversion charts, standard envelope sizes in the USA, Europe, Canada and Asia, and much more. This hardworking handbook is compact and accessible and is a must-have for any graphic designer.